Microarray assessment of N-glycan-specific IgE and IgG profiles associated with Schistosoma mansoni infection in rural and urban Uganda - Nkurunungi, Gyaviira (Sci Rep, 2019)
Core β-1,2-xylose and α-1,3-fucose are antigenic motifs on schistosome N-glycans, as well as prominent IgE targets on some plant and insect glycoproteins. To map the association of schistosome infection with responses to these motifs, we assessed plasma IgE and IgG reactivity using microarray technology among Ugandans from rural Schistosoma mansoni (Sm)-endemic islands (n = 209), and from proximate urban communities with lower Sm exposure (n = 62). IgE and IgG responses to core β-1,2-xylose and α-1,3-fucose modified N-glycans were higher in rural versus urban participants. Among rural participants, IgE and IgG to core β-1,2-xylose were positively associated with Sm infection and concentration peaks coincided with the infection intensity peak in early adolescence. Responses to core α-1,3-fucose were elevated regardless of Sm infection status and peaked before the infection peak. Among urban participants, Sm infection intensity was predominantly light and positively associated with responses to both motifs. Principal component and hierarchical cluster analysis reduced the data to a set of variables that captured core β-1,2-xylose- and α-1,3-fucose-specific responses, and confirmed associations with Sm and the rural environment. Responses to core β-1,2-xylose and α-1,3-fucose have distinctive relationships with Sm infection and intensity that should further be explored for associations with protective immunity, and cross-reactivity with other exposures.